Democracia e discurso autorreferencial : representações em disputa nas páginas da grande imprensa carioca (1955-1960) - Krilow, Letícia Sabina Wemeier (2022)
This dissertation intends to analyze how the Carioca press from Rio de Janeiro city (Correio da Manhã, Jornal do Brasil, O Globo, and Última Hora) represented democracy in Brazil by the second half of the 1950s (1955-1966) and its institutional role in the democratic regime. Between 1955 and 1960, the country was amid a period of intensified transformation, both political and social, as well as economic. Such transformations normally meant interference in the way papers perceived and represented politics and in the papers’ institutional roles in democracy. As shown in extensive literature, the changes in the Carioca press of that time tend to alter how these periodicals are symbolically developed, mainly in politics and their relation to politics. A movement in the press seems to lead to the strengthening of this journalistic institution in the public debate and the way that it seeks to build its role in politics. At the same time, politics undergoes a process of re-articulation because of the Electoral Code (1945), which regulates elections and electoral registrations throughout the country. However, this theme still has not been researched in such terms. It is relevant to analyze how the selected newspapers perceived democracy as well as how they sought to legitimately establish themselves in public debate through distinctive roles. For this analysis, we sought theoretical references that allowed us to see the symbolic and cultural productions, in which journalism is found, as relatively independent institutions. The analysis also takes into consideration the internal specificities of the press as an institution and how the papers related to each other while responding to external pressure, mainly in politics. It is a complex relationship that cannot be simply viewed as hierarchical or as mere subordination from the papers to political parties or groups. It has to be seen dynamically. This analysis validates the theory in Pierre Bourdieu's field of research and the dialogue we intend to establish between Roger Chartier’s concept of social representations and Sandra Jovchelovitch. The methodology consists of content analysis. We conclude that the newspapers in the eagerness to defend their positions, their editorial line and their relevance to the democratic regime, from different public functions (interpreter of collective thought, speak for the collectivity, defender of popular interests, watchdog of the public power, assist public affairs), ended up trying to impose their worldview on others. Thus, we argue that internal disputes in the field and also with agents from other fields, such as politics, generated as a by-product a negative view of the current democracy, in which the democratic regime itself is not directly criticized, but, at times, the political capacity of the people is questioned, their public figures, their main institutions (parties, voting and elections) are condemned. Since this representation could be appropriated by different groups, in different ways, especially to legitimize extralegal measures that would lead to the overthrow of the regime.